Churchman's Inquirers as Design Templates for Knowledge Management Systems. - PARRISH, JR., JAMES L.; COURTNEY, JR., JAMES F. (Communications of the ACM, 2009)
The article discusses inquiring systems and knowledge management systems. The authors discusses "The Design of Inquiring Systems," a book by philosopher C. West Churchman, in which philosophies of various philosophers such as John Locke and Immanuel Kant are translated into a design language to form inquiring systems which will create knowledge. It is noted that each philosopher's view on gathering knowledge differs based on their world view. Also discussed is inquiring systems theory as a basis for information systems (IS) research and creating an object-orienting computing language based on Churchman's language of design and inquiry.